1995
DOI: 10.1093/gerona/50a.4.b193
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Expression of the Molecular Markers of Dopaminergic Neuronal Atrophy in the Aging Rat Brain

Abstract: Expression of mRNAs encoding the dopamine transporter (DAT) and tyrosine hydroxylase (TH) in dopaminergic neurons of the substantia nigra (SN) was examined in young and aged Fischer 344 rats by in situ hybridization. Quantitative analysis revealed a statistically significant decline in both DAT and TH mRNA expression in 24-month-old rats in comparison to 6-month-old rats. In addition, it was noted that DAT mRNA expression tended to decrease by 18 months, while TH mRNA reduction did not occur until 24 months. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…This was especially evident in 28-month-old control rats which had low GAP-43 mRNA [50] and high GAP43 protein levels in the hippocampal formation, suggesting a low turnover level for GAP-43 protein. Interestingly, the seizure activity caused a temporary reduction in GAP-43 levels in these old rats, suggesting that the seizure activity may have increased the turnover rate of GAP-43 protein in this age group and restored the GAP-43 mRNA/GAP-43 protein relationship to values of younger animals.…”
Section: Discussionmentioning
confidence: 92%
“…This was especially evident in 28-month-old control rats which had low GAP-43 mRNA [50] and high GAP43 protein levels in the hippocampal formation, suggesting a low turnover level for GAP-43 protein. Interestingly, the seizure activity caused a temporary reduction in GAP-43 levels in these old rats, suggesting that the seizure activity may have increased the turnover rate of GAP-43 protein in this age group and restored the GAP-43 mRNA/GAP-43 protein relationship to values of younger animals.…”
Section: Discussionmentioning
confidence: 92%
“…Changes in extralimbic areas also are likely to occur during aging, because a shorter latency to onset for convulsive seizures and sustained convulsive seizures was noted. Furthermore, data suggest that neuromodulatory systems may be altered during aging (38,(50)(51)(52), and these systems have been shown to regulate epileptiform activity in vitro, as well as seizure severity/susceptibility and spread in vivo (53)(54)(55)(56). However, the possibility cannot be discounted that agingrelated changes in peripheral organs (e.g., renal clearance), the blood-brain barrier, and/or pharmacokinetics also are involved with producing the altered EEG and behavioral characteristics in aged rodents during kainate-induced status epilepticus.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in striatal dopamine D 1 (Suhara et al 1991;Nabeshima et al 1994;Wang et al 1998) and D 2 (Morgan et al 1987;Antonini and Leenders 1993;Rinne et al 1993;Mesco et al 1993) receptors with age (Cross et al 1984;Lai et al 1987;Rinne 1987;Seeman et al 1987;Rinne et al 1990;Volkow et al 1996) and a loss of binding of dopamine transporter ligands (Bannon et al 1992;Himi et al 1995;Ma et al 1999a) has been reported. D 1 and D 2 receptor density was not decreased in SN (De Keyser et al 1990, but a decrease in dopaminergic uptake sites of putamen (De Keyser et al 1990) and a decrease in postmortem brain dopamine content with aging has been observed (Carlsson and Winblad 1976).…”
Section: Introductionmentioning
confidence: 99%